The Evolution of the Jilbāb in Indonesia: From Cultural Tradition to Symbol of Religious Identity and Political Resistance - Ana Rahmawati; M Mukhsin Jamil; Akhmad Arif Junaidi (Women, Education, and Social Welfare, 2026)
This study examines the transformation of the jilbāb in Indonesia, exploring its evolution from pre-Islamic head-covering traditions to its current role as a symbol of piety, resistance, and cultural identity. Through a qualitative historical analysis combined with Critical Discourse Analysis (CDA), the study traces the dynamic interaction of cultural, religious, and political factors that have shaped the jilbāb over time. The results show that local practices such as rimpu in Bima, tudung among the Bugis, and tengkuluk in Jambi were integrated into Islamic norms, creating hybrid forms of modest dress. The New Order regime’s prohibition of the jilbāb in public schools politicized the garment, transforming it into a symbol of resistance against state control. In the Reformasi era, greater civil liberties and the rise of Islamic movements led to the resurgence of the jilbāb as a symbol of religious identity, while also being commodified in the expanding Muslim fashion industry. This study demonstrates that the jilbāb in Indonesia is not a static symbol but one that has been continuously reshaped by political, cultural, and religious forces. By offering a diachronic analysis of the jilbāb, this research contributes to broader discussions on religious symbolism, gender norms, and the role of modest dress in Indonesian society, highlighting its significance as both a personal and political statement.